PERFORMANCE OPTIMIZATION OF UNIT 1 SATRESKRIM IN THE INVESTIGATION OF THE CRIMINAL ACTION AT POLRES PEKALONGAN FOR THE PRECISION LAW ENFORCEMENT - Martin Samuel Sibarani (Indonesian Journal of Police Studies, 2022)
The constitution of the Republic of Indonesia is the fundamental law in the Republic of Indonesia. According to Law No. 2 of 2022 about The Police of Republic of Indonesia, it is explained that the main duties of the police of republic of Indonesia are to protect, to serve people and to enforce the law. Polres Pekalongan as a police service provider in the region of Pekalongan also carries out the law enforcement activities. The law enforcement in the resort level is carried by Criminal Investigation Unit. According to the percentage of completion of the criminal act, curat (pencurian dengan pemberatan) decreased significantly. As a unit which deals with these cases, Unit 1 Satreskrim become researcher’s place to do the research. The research approach in this thesis uses qualitative approach with field study method. The findings when performing the research show that the implementation of investigation activities has not followed the applicable legal basis. Investigation plan is seldom issued as well with the reason that the investigation is temporary adjusting the findings in the field. Besides, there are several factors which can hinder Unit 1 in implementing investigation. The researcher found several internal factors which can find, the number of personnel does not meet the DSP, the Satreskrim members who have done vocational training (dikjur) are very few in number and very limited infrastructure. On the other hand, the external factors which can hinder the investigation are very wide jurisdiction and the covid pandemic which is not over. Therefore, a solution is needed in optimizing curat criminal act investigation activities due to the precise law enforcement in Polres Pekalongan jurisdiction. The conclusion of this thesis is that the implementation of investigations done by Unit 1 Satreskrim Polres Pekalongan can be optimized. All this time the investigation was not considered optimal due since the percentage of completion of criminal cases was decreasing and there were no efforts to maximize force and opportunities and to minimize the weakness and threat thus the researcher provides solutions in form of problem solving towards the problem and some advices. Keywords: Optimization, Investigation, Curat Criminal Act